Depletion of myeloid-derived suppressor cells sensitizes murine multiple myeloma to PD-1 checkpoint inhibitors - Qiang Wang; Qing Yi; Wei Xiong; Rui Duan; Jianfei Qian; Liuling Xiao; Miao Xian; Pan Su; Chuanchao Zhang; Yabo Li; Ling Zhong; Chengyun Zheng (Journal for ImmunoTherapy of Cancer)
Background Cancer immunotherapy using immune checkpoint blockade (ICB) has revolutionized cancer treatment. However, patients with multiple myeloma (MM) rarely respond to ICB. Accumulating evidence indicates that the complicated tumor microenvironment (TME) significantly impacts the efficacy of ICB therapy. Therefore, investigating how TME components in MM influence ICB treatment is urgent.Methods We employed two well-established murine myeloma models, 5TGM1 and Vk*MYC, by intravenously injecting 5TGM1 or Vk*MYC cells into mice, respectively, to determine ICB therapeutic efficacy in MM. Total mouse IgG or Ig2b ELISA or QuickGel split beta SPE kits and in vivo bioluminescent imaging were used to monitor MM tumor burden. Cytometry by time of flight (CyTOF) was used to quantify MM TME components. T cell proliferation and function were detected using flow cytometry. Peptide-Fc fusion proteins were used to deplete myeloid-derived suppressor cells (MDSCs). MMDTR, Foxp3DTR, CD4 KO and CD8 KO mice were used to elucidate the underlying mechanisms. Gene expression levels in human MM were analyzed using Gene Expression Omnibus public datasets.Results We found that programmed cell death protein 1 (PD-1) antibody treatment had a therapeutic effect in 5TGM1 mice; it was ineffective in Vk*MYC mice. CyTOF indicated that the bone marrow (BM) of both models was inflamed, suggesting that immune suppressive cells might be inhibiting the reactivation of T cells in the BM. We observed higher numbers of MDSCs, regulatory T (Treg) cells, and tumor-associated macrophage (TAMs) in myeloma BM compared with that of tumor-free mice. Specifically, depleting MDSCs, but not Treg cells or TAMs, sensitized Vk*MYC mice and enhanced the response of 5TGM1 mice to PD-1 ICB, which was dependent on CD8+ but not CD4+ T cells. MDSCs, especially M-MDSCs and CD84+ MDSCs, significantly inhibited the activation and cytotoxic cytokine production of CD8+ T cells in vitro. Moreover, database profiling of patient BM revealed a negative correlation between MDSCs signature genes and cytotoxic CD8+ T cell signature genes, with post-maintenance patients with myeloma displaying a higher ratio of cytotoxic CD8+ T cell to MDSCs signature genes compared with pretreated patients.Conclusion Our study highlights the potential of MDSCs depletion in enhancing the sensitivity of patients with myeloma to PD-1 ICB therapy.